Broadening minds: exploring intercultural understanding in adult EFL learners - Cruz Arcila, Ferney (Colombian Applied Linguistics Journal, 2007)
Our current globalized world has become a space where many cultures are in permanent contact. Now, we are living in an interconnected world that requires us to be tolerant with others. This article describes some processes through which adult EFL learners developed intercultural understanding. This research aimed to provide clear examples of how significant and necessary it is to give foreign language learners the chance to become aware of the foreign culture while they are becoming proficient in the target language. In addition, this paper also accounts for some kinds of intercultural connections the students make between their native culture and the target one. Through a careful analysis of the data collected, this qualitative case study shows that by implementing different types of pedagogical strategies the students are able to go beyond superficial ideas about the target culture which help them become more open-minded towards other forms of perceiving reality.